2020
DOI: 10.21203/rs.3.rs-94568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnoveterinary Practices of Medicinal Plants and Non-plant Remedies Used in Animal Health Management in Dawuro Zone, Southern Ethiopia

Abstract: Background: Ethnoveterinary medicine is frequently used for treating various livestock diseases by many different ethnic groups in Ethiopia. To this end, the indigenous knowledge on medicinal plants and non-plant remedies has not been systematically documented and studied in the Dawuro zone. Therefore, a community based cross-sectional study design was conducted from November, 2017 to September, 2018 in order to identify and document medicinal plants and non-plant ethnoveterinary practices in Dawuro zone, Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(58 reference statements)
2
1
1
Order By: Relevance
“…The recovery time for majority of EVM treatments in the current study was 2–3 days. Similar findings were also reported by ( 8 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The recovery time for majority of EVM treatments in the current study was 2–3 days. Similar findings were also reported by ( 8 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…The current research identified 15 plant species from 10 families that have veterinary use. However, this number is significantly less than the 46 species reported by ( 8 ) in Southern Ethiopia and the 31 plant species reported by ( 20 ) in north central Nigeria. Most of the species in EVM came from the Fabaceae family, which contributed four species.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations